Predator kairomones elicit bold, exploratory behaviours in juvenile bluegill, Lepomis macrochirus - Ramsaran, V.D.; Jackson, B.L.; Bucciol, S.M.; Puniani, T.; Lawrence, M.J.; Elvidge, C.K. (Animal behaviour, 2021)
Behavioural responses of animals are often placed conceptually along some axis characterized by the extremes, e.g. bold versus shy or timid. Ecological and evolutionary pressures can be associated with increased frequencies of different behavioural patterns that are also subject to intrinsic factors such as differing metabolic requirements or cognitive abilities. We exposed individual wild-caught juvenile bluegill, Lepomis macrochirus, to kairomones from predatory northern pike, Esox lucius, or to lake water controls during a Z-maze arena assay commonly used to assess relative levels of boldness and exploratory behaviours. Fish were subsequently lethally sampled for liver and brain mass to obtain estimates of relative body condition (hepato-somatic index, HSI) and cognitive capacity (brain-somatic index, BSI), as well as the state of the gallbladder, to test for relationships between these indices and observed boldness-related behaviours. Using principal components analysis (PCA) we identified a boldness–exploration syndrome in bluegill independent of chemical treatment and body metrics where bolder fish emerged from a start chamber in less time, travelled farther through the maze and crossed more lines than less bold fish. Bluegill exposed to kairomones were bolder on average than their counterparts in the control treatment independent of body metrics, suggesting that elevated risk levels indicated by predator kairomones can elicit behavioural responses consistent with boldness, exploration and risk taking. The role of relative cognitive ability in the expression of boldness and exploration is equivocal and may be resolved through repeated assays on individuals at different risk levels. •Behavioural responses to risky cues can vary along a shy–bold continuum.•Bold-type responses may confer greater benefits under low-risk conditions.•Exposure to kairomones elicited more exploratory behaviours in juvenile bluegill.•Bold-type exploratory behaviours were not related to energy stores or brain size.•Background chemical information can significantly influence behavioural patterns.